Green Manufacturing in the Printing Industry: Research Trends, Implementation Challenges, and a Future Roadmap - Rindi Antika Jubaedah; Dianta Mustofa Kamal (International Journal of Science and Society (IJSS), 2026)
The printing industry plays a vital role in communication, education, and the creative economy, yet it is also associated with considerable environmental impacts due to high energy consumption, reliance on petroleum-based raw materials, intensive water use, and significant waste generation. In response to increasing societal pressure, regulatory demands, and sustainability-oriented market expectations, Green Manufacturing has emerged as a critical paradigm to reduce the ecological footprint of the printing sector while maintaining its economic and social functions. This study aims to systematically review the existing body of knowledge on Green Manufacturing in the printing industry by identifying dominant research trends, examining key implementation challenges, and proposing a future-oriented research and policy roadmap. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, synthesizing 35 peer-reviewed international journal articles published between 2014 and 2024 and indexed in major scientific databases. The findings reveal three dominant research streams: (1) innovation in sustainable raw materials, including plant-based inks and recycled or bio-based substrates; (2) process and energy efficiency improvements through digital printing technologies and waterless printing systems; and (3) the adoption of circular economy principles for waste reduction and resource recovery. Despite technological progress, implementation remains constrained by high initial investment costs, technical performance gaps of green materials, fragmented sustainability standards, and limited awareness among consumers and small and medium-sized enterprises (SMEs). Based on identified gaps, this paper proposes a future roadmap emphasizing locally sourced eco-materials, integration of AI and IoT for process optimization, development of globally harmonized sustainability standards, and circular economy–driven business models. By positioning Green Manufacturing as a socio-technical transformation rather than a purely technological shift, this study contributes strategic insights for researchers, industry practitioners, and policymakers seeking to accelerate a sustainable transition in the printing industry.